Physico-chemical characteristics of Chok Anan mango fruit after hot water treatment - Ding, Phebe; Mijin, Salumiah (Universiti Putra Malaysia Press, 2013)
Mango fruit is prone to postharvest disease, especially anthracnose and stem end rot. Hot water dip (HWD) treatment has been used to control postharvest disease in fruit but little information about the response of Chok Anan mango fruit towards HWD treatment. This study was conducted to determine optimum duration of HWD in controlling postharvest diseases. Mature green Chok Anan mango fruit were treated at 26 and 55 oC for 5, 15 and 25 min and fruits at ripening stage 1, 3 and 5 were analyzed for peel colour, flesh firmness, soluble solids concentration (SSC), ascorbic acid, pH, titratable acidity, disease incidence and heat induced injury. HWD treatment did not affect peel colour, SSC, ascorbic acid, pH and titratable acidity and induced heat injury to the fruit. Disease incidence of ripening stage 5 (fully ripened) fruit reduced significantly after HWD. In addition, the fruit underwent normal ripening as ripening progressed. It is concluded that combination of 55oC hot water for 5 min can be used as postharvest disinfestation treatment for Chok Anan mango fruit while maintaining physico-chemical characteristics of fruit.